PENGARUH TEKNIK SHAPING TERHADAP PENINGKATAN KEMANDIRIAN PERSONAL HYGIENE TANGAN SISWA TUNAGRAHITA DI SKh MADINA KOTA SERANG - Anisa Handayani; Sistriadini Alamsyah Sidik; Siti Musayaroh (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to determine the independence of personal hygiene of hands of intellectual disabilities students at SMPLB level in SKh Madina, Serang City, using the shaping techniques. This research is experimental research with a single subject research (SSR) approach with an A-B-A design. The subjects in this research were two SMPLB students with intellectual disabilities. The target behavior in this research is the ability to wash hands. Data collection techniques were obtained by observation and action tests. The data analysis used is descriptive statistical analysis with graphic presentation. Based on the research results, the average result of the first subject's hand washing ability in the baseline-1 phase was 25%, while the result of the second subject was 31.25% because this phase was a natural condition before the intervention or treatment was given. In the intervention phase (B), the average data acquisition results were 85.05% for the first subject (H) and data acquisition was 87.14% for the second subject (I), these results were obtained after the subjects received the intervention. Meanwhile, in the baseline- 2 phase, the average data acquisition results were 68.75% for the first subject (H) and data acquisition was 75% for the second subject (I), these results were the natural results of the subjects after being given intervention or treatment. From the results of data obtained in this research, it can be concluded that the use of shaping techniques for intellectual disabilities students can increase the independence of personal hygiene of nails and hands of intellectual disabilities students at SMPLB level at SKh Madina, Serang City.